Dialectology - Chambers, J. K. (Cambridge textbooks in linguistics., 1998)
When first published in 1980, Dialectology broke new ground by integrating urban dialectology (sociolinguistics), dialect geography and spatial variation into a cohesive discipline. In this second edition, the authors take account of the renaissance of dialect research in the last twenty years. They offer new sections on dialectometry and mapping variability, a revised section on dialect geography as well as updates of other recent developments. A reliable textbook for over seventeen years, this new edition will continue to serve the needs of undergraduates and individual scholars with its com.